Expanding the Clinical Spectrum of Phenotypes Caused by Pathogenic Variants in PLOD2. (4th January 2018) - Leal, Gabriela Ferraz; Nishimura, Gen; Voss, Ulrika; Bertola, Débora Romeo; Åström, Eva; Svensson, Johan; Yamamoto, Guilherme Lopes; Hammarsjö, Anna; Horemuzova, Eva; Papadogiannakis, Nikos; Iwarsson, Erik; Grigelioniene, Giedre; et al.
ABSTRACT: Osteogenesis imperfecta (OI) is a strikingly heterogeneous group of disorders with a broad range of phenotypic variations. It is also one of the differential diagnoses in bent bone dysplasias along with campomelic dysplasia and thanatophoric dysplasia and can usually be distinguished by decreased bone mineralization and bone fractures. Bent bone dysplasias also include syndromes such as kyphomelic dysplasia (MIM:211350) and mesomelic dysplasia Kozlowski‐Reardon (MIM249710), both of which have been under debate regarding whether or not they are a real entity or simply a phenotypic manifestation of another dysplasia including OI. Bruck syndrome type 2 (BRKS2; MIM:609220) is a rare form of autosomal recessive OI caused by biallelic PLOD2 variants and is associated with congenital joint contractures with pterygia. In this report, we present six patients from four families with novel PLOD2 variants. All cases had multiple fractures. Other features ranged from prenatal lethal severe angulation of the long bones as in kyphomelic dysplasia and mesomelic dysplasia Kozlowski‐Reardon through classical Bruck syndrome to moderate OI with normal joints. Two siblings with a kyphomelic dysplasia‐like phenotype who were stillborn had compound heterozygous variants in PLOD2 (p.Asp585Val and p.Ser166*). One infant who succumbed at age 4 months had a bent bone phenotype phenotypically like skeletal dysplasia Kozlowski‐Reardon (with mesomelic shortening, camptodactyly, retrognathia, cleft palate, skin dimples, but also with fractures). He was homozygous for the nonsense variant (p.Trp561*). Two siblings had various degrees of Bruck syndrome caused by the homozygous missense variant, p.His687Arg. Furthermore a boy with a clinical presentation of moderate OI had a possibly pathogenic homozygous variant p.Trp588Cys. Our experience of six patients with biallelic pathogenic variants in PLOD2 expands the phenotypic spectrum in the PLOD2‐ related phenotypes. © 2017 American Society for Bone and Mineral Research. Abstract :